Australian education journals: quantitative and qualitative indicators - Haddow, Gaby; Genoni, Paul (Australian Library and Information Association, 2009)
This paper reports on a study which applied citation-based measures to Australian education journals. Citations data were drawn from two sources, Web of Science and Scopus, and these data were used to calculate each journal's impact factor, h-index, and diffusion factor. The rankings resulting from these analyses were compared with draft rankings assigned to the journals for Excellence for Research in Australia (ERA). Scopus emerged as the citation source most advantageous to these journals and some consistency across the citation-based measures was found.